Design of a Web-Based Appointment for Patient of Optometry Department at El-Beida Hospital, Libya. - Mohamed, Omran A. H. (2011)
It has shown that the advent of World Wide Web has revolutionized the business processes and assists the information dissemination especially in hospital all over the world. This project research on the problem that is currently facing the patients of optometry department in El-Beidal hospital Libya where patients are finding it difficult to receive medical care due to the old method of medical treatment that are in practice. A prototype is developed to help the patients in communicating and booking appointment with medical officers in Optometry Department of El-Beidal hospital Libya irrespective of time and their location. The system was tested by the prospective users and found that it is easy to use.